2001
DOI: 10.1074/jbc.m102394200
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of S2V, a Novel Putative Siglec That Contains Two V Set Ig-like Domains and Recruits Protein-tyrosine Phosphatases SHPs

Abstract: We describe the molecular cloning and characterization of S2V, a novel sialic acid binding immunoglobulin-like lectin. The cDNA of S2V encodes a type 1 transmembrane protein with four extracellular immunoglobulin-like (Ig-like) domains and a cytoplasmic tail bearing a typical immunoreceptor tyrosine-based inhibitory motif (ITIM) and an ITIM-like motif. A unique feature of S2V is the presence of two V-set Ig-like domains responsible for the binding to sialic acid, whereas all other known siglecs possess only on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 50 publications
1
27
0
Order By: Relevance
“…Immunoprecipitation experiments with transfected RBL cells together with pull-downs using GST-Siglec-5 fusion proteins showed that phosphorylated WT Siglec-5 and the Y2A mutant were able to recruit both SHP-1 and SHP-2, whereas little or no interaction was seen with the phosphorylated Y1A mutant. These findings show that the membrane proximal motif is dominant over the distal motif for interactions with proteintyrosine phosphatases and is consistent with previous findings made with other CD33-related siglecs including CD33/Siglec-3, human Siglec-L1, and mouse Siglec-E (6,7,9,12,13,24).…”
Section: Discussionsupporting
confidence: 93%
“…Immunoprecipitation experiments with transfected RBL cells together with pull-downs using GST-Siglec-5 fusion proteins showed that phosphorylated WT Siglec-5 and the Y2A mutant were able to recruit both SHP-1 and SHP-2, whereas little or no interaction was seen with the phosphorylated Y1A mutant. These findings show that the membrane proximal motif is dominant over the distal motif for interactions with proteintyrosine phosphatases and is consistent with previous findings made with other CD33-related siglecs including CD33/Siglec-3, human Siglec-L1, and mouse Siglec-E (6,7,9,12,13,24).…”
Section: Discussionsupporting
confidence: 93%
“…We also consider potential connections to the previously described human-specific mutation involving sialic acid biology and search the human genome for Siglec-like pseudogenes, several of which turn out to have independent mutations replacing the "essential" arginine residue. After this work was completed, another group independently reported the cloning of the same molecule, which they called S2V, a "putative" Siglec (24). Our study shows that the "essential" arginine residue, which was mutated to cysteine specifically in the human lineage, is required for easily detectable sialic acid-dependent recognition typical of previously reported Siglecs.…”
mentioning
confidence: 59%
“…The presence of putative tyrosine-based signaling motifs in the cytosolic tail suggests that the great ape orthologs are (and that the human ancestral Siglec-L1 could have been) involved in the regulation of homeostasis of sialylated glycoconjugates within the lumen of some organs. Indeed, others have shown that the membrane-proximal tyrosine-based motif of this molecule can interact with the tyrosine phosphatases SHP-1 and SHP-2 (24). The expression of this molecule on surfaces that come into contact with the environment also suggests its possible involvement in microbial infection (e.g.…”
Section: The Human Genome Contains Several Siglec Pseudogenes With Inmentioning
confidence: 99%
“…A previous study (31) showed that Siglec-XII (called S2V in that paper) binds to the tyrosine phosphatases SHP-1 and SHP-2 in a phosphorylation-dependent manner (co-immunoprecipitation worked only in the presence of pervanadate). Despite the R122C mutation, Siglec-XII was phosphorylated by the kinase c-Src.…”
Section: Discussionmentioning
confidence: 88%